Auditory Brainstem Response in Term and Preterm Infants with Neonatal Complications: The Importance of the Sequential Evaluation - Silva, Daniela da; Lopez, Priscila; Mantovani, Jair Cortez (International Archives of Otorhinolaryngology, 2015)
Introduction Literature data are not conclusive as to the influence of neonatal complications in the maturational process of the auditory system observed by auditory brainstem response (ABR) in infants at term and preterm.Objectives Check the real influence of the neonatal complications in infants by the sequential auditory evaluation.Methods Historical cohort study in a tertiary referral center. A total of 114 neonates met inclusion criteria: treatment at the Universal Neonatal Hearing Screening Program of the local hospital; at least one risk indicator for hearing loss; presence in both evaluations (the first one after hospital discharge from the neonatal unit and the second one at 6 months old); all latencies in ABR and transient otoacoustic emissions present in both ears.Results The complications that most influenced the ABR findings were Apgar scores less than 6 at 5 minutes, gestational age, intensive care unit stay, peri-intraventricular hemorrhage, and mechanical ventilation.Conclusion Sequential auditory evaluation is necessary in premature and term newborns with risk indicators for hearing loss to correctly identify injuries in the auditory pathway.
Keywords: neonatology; evoked potentials; auditory brainstem